2008
DOI: 10.1128/jvi.01822-07
|View full text |Cite
|
Sign up to set email alerts
|

Immune Serum Produced by DNA Vaccination Protects Hamsters against Lethal Respiratory Challenge with Andes Virus

Abstract: Hantavirus pulmonary syndrome (HPS) is a highly pathogenic disease (40% case fatality rate) carried by rodents chronically infected with certain viruses within the genus Hantavirus of the family Bunyaviridae. The primary mode of transmission to humans is thought to be inhalation of excreta from infected rodents; however, ingestion of contaminated material and rodent bites are also possible modes of transmission. Person-to-person transmission of HPS caused by one species of hantavirus, Andes virus (ANDV), has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 25 publications
4
87
0
1
Order By: Relevance
“…[50][51][52][53] Finally, passive immunization of Syrian hamsters with neutralizing antibodies against ANDV-encoded Gn and Gc that were produced in other species (macaques, rabbits) confers protective immunity against lethal challenge with ANDV. 11,45,51,54 Collectively, these data support the concept that strong induction of neutralizing antibodies against envelope glycoproteins represents a prime goal in hantavirus vaccine development.…”
Section: Role Of Antiviral Immune Responses In Hantavirus-induced Patsupporting
confidence: 61%
See 2 more Smart Citations
“…[50][51][52][53] Finally, passive immunization of Syrian hamsters with neutralizing antibodies against ANDV-encoded Gn and Gc that were produced in other species (macaques, rabbits) confers protective immunity against lethal challenge with ANDV. 11,45,51,54 Collectively, these data support the concept that strong induction of neutralizing antibodies against envelope glycoproteins represents a prime goal in hantavirus vaccine development.…”
Section: Role Of Antiviral Immune Responses In Hantavirus-induced Patsupporting
confidence: 61%
“…found a protective effect of anti-ANDV sera even as late as 5 days after virus infection. 11 On the basis of these findings, one can speculate about the future establishment ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Passive Immunizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingestion could occur when several bank voles share a common food source. Hooper et al have recently shown that Andes hantavirus is infectious to hamsters when administered by intragastric injection and speculate that ingestion of contaminated material might be a mode of transmission to humans (18). We have shown that intranasal inoculation of saliva, urine, or feces enables subsequent detection of viral RNA in all types of excretions, which indicates that virions excreted by different routes do not show restricted tropism for particular tissues.…”
Section: Discussionmentioning
confidence: 75%
“…The hantavirus glycoproteins are typically thought to be the principal targets of neutralizing antibodies (1,8,39,51), and although a few potential vaccine candidates have been evaluated with various degrees of success, largely in infection rather than disease models (2,7,10,21,24,25,35,56,60,72,73), the mechanism of protection against hantavirus infections remain unidentified. Here we constructed an attenuated, replication-competent recombinant VSV expressing the ANDV GPC in order to investigate its efficacy as a hantavirus vaccine in the Syrian hamster HPS disease model and to gain further insight into the mechanism of protection against lethal ANDV infection.…”
Section: Discussionmentioning
confidence: 99%